Experimental Study on the Transition Characteristics and Criterion From Wall-Peak to Core-Peak Phase Distribution in Vertical Rod Bundles - Ren, Quan-yao; Pu, Zengping; Chen, Ping; Pan, Liang-ming; Zhu, Fawen; Zheng, Meiyin; Wang, Haoyu; Wei, Lie; He, Hui (Frontiers in Energy Research, 2021)
Aiming at understanding the phase distribution characteristics and developing the transition criterion from wall-peak to core-peak phase distribution in a rod bundle channel, air–water two-phase flow experiments were conducted in 5 × 5 rod bundles in the Interfacial Evolution Research Facility at Chongqing University (IERFC). Based on the experimental data, the influences of gas velocity, liquid velocity, mixing vane spacer grid (MVSG), and geometrical size on phase distribution have been analyzed in detail. With the increasing superficial gas velocity and decreasing liquid velocity, the wall-peak phase distribution turned to core-peak. The wall-peak phase distribution was enhanced by an MVSG, and the transition from the transitional phase distribution to the wall-peak phase distribution appeared when the air–water mixture flowed through the MVSG. The gap size was the key factor for the transition of phase distribution in rod bundles. Moreover, the transition criterion from wall-peak to core-peak phase distribution was developed based on present experimental data and the data in the literature, which was also verified based on the limited data. More experiments were recommended to focus on the detailed phase distribution in the rod bundle channel with different geometrical sizes.